Compensating regulation of land: UK and Singapore compared. Issue 2 (8th July 2019) - Ti, Edward Seng Wei
Abstract : Purpose: The paper aims to analyse and compare how UK and Singapore deal with compensation with respect to regulation of land (short of a physical taking). The purpose is to determine whether the non-compensation in each jurisdiction is justified. Design/methodology/approach: A comparative method using case law, statutes and secondary material across both jurisdictions (as well as some US case law) is adopted. Findings: Both the UK and Singapore do not provide compensation when land is affected by regulation, so long as a physical taking has not occurred. Partly because of the abolition of development rights in the UK since 1947, this position may be justified. Conversely, Singapore's Master Plan seeks a great deal of public reliance and advertises development potential, and non-compensation is not defensible. Originality/value: There is very limited analysis on regulatory effects of land in the UK, and virtually none in Singapore. This would also be the first attempt to compare this aspect of the UK and Singapore's planning regime.